2014
DOI: 10.1007/s00109-014-1180-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of HIF1α in renal cell carcinoma tumorigenesis

Abstract: The transcription factor HIF1α is implicated in the development of clear cell renal cell carcinoma (ccRCC). Although HIF1α was initially believed to be essential for ccRCC development, recent studies hypothesize an oncogenic role for HIF2α in ccRCC, but a tumor suppressor role for HIF1α [1], leading to uncertainty as to the precise roles of the different HIF transcription factors in this disease. Using evidence available from studies with human ccRCC cell lines, mouse xenografts, murine models of ccRCC, and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 98 publications
(117 reference statements)
4
79
1
Order By: Relevance
“…4,39 To determine whether this growth factor is involved in MARCKS signaling, we evaluated VEGFA-stained cells in the xenograft tumors and found parallel reduction of VEGFA and MARCKS expression in tumors derived from MARCKS-silenced 786-O cells (Figure 4a). To validate this finding in human RCC, samples from the GSE53757 data set ( n = 144) were grouped into high- and low-MARCKS expression using the median as a cutoff and subjected to Wilcoxon–Mann– Whitney test on the VEGFA expression levels of the two groups; these data showed a significantly higher level of VEGFA in the high-MARCKS subset (Figure 4b; W = 4902, P -value <0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,39 To determine whether this growth factor is involved in MARCKS signaling, we evaluated VEGFA-stained cells in the xenograft tumors and found parallel reduction of VEGFA and MARCKS expression in tumors derived from MARCKS-silenced 786-O cells (Figure 4a). To validate this finding in human RCC, samples from the GSE53757 data set ( n = 144) were grouped into high- and low-MARCKS expression using the median as a cutoff and subjected to Wilcoxon–Mann– Whitney test on the VEGFA expression levels of the two groups; these data showed a significantly higher level of VEGFA in the high-MARCKS subset (Figure 4b; W = 4902, P -value <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Under normoxic conditions, the VHL protein contributes to the degradation of the α -subunit of hypoxia-induced factors (HIFs). Because of Q3 the inactivation of the VHL gene, which is common in clear-cell RCC, the HIF-α proteins accumulate and induce expression of their target genes, such as vascular endothelial growth factor (VEGF) and others, 3,4 which are involved in angiogenesis; therefore, anti-angiogenic therapies have played a pivotal role in RCC treatment. 5 For metastatic RCC in particular, the two standard targets are the VEGF receptor and mammalian target of rapamycin (mTOR), a downstream component in the phosphoinositide 3-kinase (PI3K)/AKT pathway known to upregulate HIF-1α activity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of malignant and normal tissues found that the expression of both HIF-1 and HIF-2 is commonly increased in a variety of human tumors, including bladder, breast, colon, glial, hepatocellular, ovarian, pancreatic, prostate, and renal tumors [102]. A variety of clinical and mechanistic data supports that HIF-1α has an important role in promoting tumorigenesis in a clinically important and large subset of human renal carcinoma (see review [103] by Gudas et al).…”
Section: Renal Tumorigenesismentioning
confidence: 99%
“…These studies argue that whereas HIF2a activity is tumor promoting, there is a selection against HIF1a expression or activity during the progression of some cases of ccRCC. On the other hand, because HIF1a is strongly expressed in single and multicellular clusters of VHL-null cells and in cystic lesions in VHL patients (4), and because transgenic overexpression of HIF1a in mouse proximal tubular epithelial cells causes a clear cell appearance, increased proliferation, and a disorganized tubular morphology (25), and because many human ccRCCs express HIF1a and HIF1a target genes (26), it may also be argued that HIF1a plays an important role in promoting ccRCC development. These studies have largely focused on fully transformed, genetically complex ccRCC cell lines derived from advanced tumors, and it remains unclear if and how HIF1a and HIF2a contribute to the earliest stages of initiation of ccRCC.…”
Section: Introductionmentioning
confidence: 99%